
= 
m1 å
k = 0


æ ç
è

n+1+k
k

ö ÷
ø

x^{k} y^{k} [ x^{nk+2} + y^{nk+2}] + 
æ ç
è

n+m
m1

ö ÷
ø

x^{m} y^{m} [x^{nm+1} + y^{nm+1}] 


+ 
n å
k = m


æ ç
è

n+k
k

ö ÷
ø

x^{k} y^{k} [x^{nk+1} + y^{nk+1}] 


= 
m1 å
k = 0


æ ç
è

n+1+k
k

ö ÷
ø

x^{k} y^{k} [ x^{nk+2} + y^{nk+2}] + 
é ê
ë


æ ç
è

n+m
m1

ö ÷
ø

+ 
æ ç
è

n+m
m

ö ÷
ø


ù ú
û

x^{m} y^{m} [x^{nm+1} + y^{nm+1}] 


+ 
n å
k = m+1


æ ç
è

n+k
k

ö ÷
ø

x^{k} y^{k} [x^{nk+1} + y^{nk+1}] 


= 
m1 å
k = 0


æ ç
è

n+1+k
k

ö ÷
ø

x^{k} y^{k} [ x^{nk+2} + y^{nk+2}] + 
æ ç
è

n+m+1
m

ö ÷
ø

x^{m} y^{m} [x^{nm+1} + y^{nm+1}] 


+ 
n å
k = m+1


æ ç
è

n+k
k

ö ÷
ø

x^{k} y^{k} [x^{nk+1} + y^{nk+1}] 


= 
m1 å
k = 0


æ ç
è

n+1+k
k

ö ÷
ø

x^{k} y^{k} [ x^{nk+2} + y^{nk+2}] + 
æ ç
è

n+m+1
m

ö ÷
ø

x^{m} y^{m} [x^{nm+1} + y^{nm+1}][x+y] 


+ 
n å
k = m+1


æ ç
è

n+k
k

ö ÷
ø

x^{k} y^{k} [x^{nk+1} + y^{nk+1}] 


= 
m1 å
k = 0


æ ç
è

n+1+k
k

ö ÷
ø

x^{k} y^{k} [ x^{nk+2} + y^{nk+2}] + 
æ ç
è

n+m+1
m

ö ÷
ø

x^{m+1} y^{m+1} [x^{nm} + y^{nm}] 


+ 
æ ç
è

n+m+1
m

ö ÷
ø

x^{m} y^{m} [x^{nm+2} + y^{nm+2}] + 
n å
k = m+1


æ ç
è

n+k
k

ö ÷
ø

x^{k} y^{k} [x^{nk+1} + y^{nk+1}] 


= 
m å
k = 0


æ ç
è

n+1+k
k

ö ÷
ø

x^{k} y^{k} [ x^{nk+2} + y^{nk+2}] + 
æ ç
è

n+m+1
m

ö ÷
ø

x^{m+1} y^{m+1} [x^{nm} + y^{nm}] 


+ 
n å
k = m+1


æ ç
è

n+k
k

ö ÷
ø

x^{k} y^{k} [x^{nk+1} + y^{nk+1}] 


